Recent highlights and future prospects on mixed-metal MOFs as emerging supercapacitor candidates. Issue 34 (11th August 2020) - Rajak, Richa; Kumar, Ravinder; Ansari, Shagufi Naz; Saraf, Mohit; Mobin, Shaikh M.
Abstract : Mixed-metallic metal–organic frameworks (M-MOFs) are prepared through one-pot-synthesis or post-synthetic modification approaches and can be easily transformed into various composites/derivatives which offer promising supercapacitor properties. Abstract : Mixed-metal metal–organic frameworks (M-MOFs) consist of at least two different metal ions as nodes in the same framework. The incorporation of a second or more metal ions provides structural/compositional diversity, multi-functionality and stability to the framework. Moreover, the periodical array of different metal ions in the framework may alter the physical/chemical properties of M-MOFs and result in fascinating applications. M-MOFs with exciting structural features offer superior supercapacitor performances compared to single metal MOFs due to the synergic effect of different metal ions. In this review, we summarize several synthetic methods to construct M-MOFs by employing various organic ligands or metalloligands. Further, we discuss the electrochemical performance of several M-MOFs and their derived composite materials for supercapacitor applications.